KOMPARASI FONEM SEGMENTAL BAHASA INDONESIA DAN BAHASA INGGRIS - Umar Saekan (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
Language is a communication tool that people use to express their feelings, communicate ideas to others. One language is the sound subsystem. In the linguistic aspects are often called phonemes. Phoneme is defined as the smallest unit of language that can differentiate meaning. It should be understood that the language sounds very important if speakers want to understand what is conveyed or communicated by other speakers in a communication network. Often times it is hard to understand the language of a speaker whose pronunciation is not clear. In fact, often a serious misunderstanding caused by unclear pronunciation. The purpose of this study is as follows (1) describe the features of segmental phonemes contained in Indonesian. (2) To describe the features of segmental phonemes contained in the English language. (3) To decrypt the contrast between segmental phonemes features Indonesian and English. Results of this study show that Indonesian has six vowels, namely: / i /, / u /, / e /, / ә /, / o /, and / a /. Number of consonants in Indonesian is twenty-two pieces, which include the / p /, / b /, / t /, / d /, / c /, / j /, / k /, / g /, / f /, / s /, / z /, / š /, / x /, / h /, / m /, / n /, / ñ /, / ŋ /, / r /, / l /, / w /, / y / . Meanwhile, the English language has the following vowels: / i :/, / i /, / e /, / ɛ /, / æ /, / a /, / u /, / ʊ /, / o /, / ͻ/, / ɒ /, / ɨ /, / ᴈ/, / ә /, and / a /. Thus, the results of this study showed that English language has fifteen pieces vowel phonemes. English language has twenty four consonant phonemes, which consists of: / p /, / b /, / t /, / d /, / k /, / g /, / tʃ /, / ʤ /, / m /, / n /, / ŋ /, / l /, / f /, / v /, / θ /, / ð /, / s /, / z/, / r /, / ʃ /, / Ʒ /, / h /, / w /, and / j /. From these data it is clear that there is a difference between vowels and consonants Indonesian with English vowels and consonants.